The Afterlife of Objects: A Material Culture Analysis of Contested Artifacts in Diasporic Communities - Shasa Indriyani; Sonia Vernanda; Abdul Malik (Enigma in Cultural, 2025)
This study investigated the complex "afterlife" of contested cultural artifacts, specifically focusing on the Indonesian keris (ceremonial dagger) held in Dutch museum collections and their significance within the Indonesian diaspora in the Netherlands. In an era of escalating repatriation debates, the profound and evolving role these objects play in the identity formation, collective memory, and cultural negotiation of diasporic communities remains a critical yet underexplored dimension. This research addressed this gap by examining how such artifacts, physically distant from their origin, continue to live vibrant, meaningful, and often contentious lives within the communities they represent. A mixed-methods approach was employed, grounded in ethnographic and material culture studies frameworks. The research was conducted between 2023 and 2024 in Amsterdam and The Hague. Data were collected through 45 in-depth, semi-structured interviews with first, second, and third-generation members of the Indonesian diaspora. This qualitative data was supplemented by a quantitative survey (n=250) to assess broader community attitudes towards the keris, museums, and cultural heritage. Thematic analysis was used for interview transcripts, while descriptive and inferential statistics were applied to survey data. The findings revealed a multifaceted and dynamic relationship with the keris. Four primary themes emerged from the qualitative data: 1) The artifact as a tangible anchor to an "imagined homeland" and ancestral lineage; 2) Significant generational shifts in meaning, moving from personal heirloom to a politicized symbol of post-colonial identity; 3) The museum as a dual site of connection and contestation; and 4) The emergence of a "digital afterlife," where online archives and social media create new forms of access and community engagement. Survey data corroborated these themes, with 88% of respondents viewing the keris as a vital symbol of their cultural identity, yet 65% expressing feelings of ambivalence or sadness regarding their location in Dutch museums. In conclusion, contested artifacts like the keris are not static relics but dynamic agents in the ongoing process of diasporic identity construction. Their afterlife is characterized by a continuous re-negotiation of meaning across generations and platforms. For diasporic communities, these objects serve as powerful conduits for memory, heritage, and political consciousness, complicating simplistic narratives of ownership and repatriation. The study concluded that understanding this diasporic dimension is essential for museums and policymakers engaging in ethical stewardship and decolonization efforts.